BOOK REVIEW: NOBEL LAUREATE PROFESSOR DR. MUHAMMAD YUNUS, (2017). A WORLD OF THREE ZEROS, THE NEW ECONOMICS OF ZERO POVERTY, ZERO UNEMPLOYMENT AND ZERO NET CARBON EMISSIONS. - Choudhury, Masud (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
This book review critically examines A World of Three Zeros by Nobel Laureate Professor Muhammad Yunus, which advocates for a new economic paradigm centered on zero poverty, zero unemployment, and zero net carbon emissions through the model of social business. While Yunus proposes social business as a moral and practical alternative to profit-maximizing capitalism, the review highlights key limitations in his framework. It notes the lack of epistemological depth and systemic methodological rigor in challenging entrenched capitalist structures. Moreover, while Yunus emphasizes microcredit and entrepreneurship, he under-theorizes the institutional transformation necessary to sustain a global order of social business. The book's optimism about technological change and development partnerships with capitalist entities also reveals contradictions in its critique of neoliberal economics. The reviewer introduces an alternative worldview based on the episteme of Tawhid and critical realism, advocating for a consciousness-based civilization rooted in unity of knowledge, justice, and moral purpose. Through diagrams and conceptual models, the review suggests that Yunus’s vision, though morally appealing, lacks the structural, philosophical, and theological grounding needed to realize sustainable transformation. A more coherent socio-economic alternative would require integrating ethics, consciousness, and systemic complementarity into the heart of development discourse.